Assessment of the Flexural Strength of No-Fines Recycled Aggregate Concrete Prisms - Rahu, Ahsan Ali; Memon, Bashir Ahmed; Oad, Mahboob; Dahri, Shakeel Ahmed; Memon, Abdul Raqeeb; Bhutto, Amjad Hussain (Engineering, Technology & Applied Science Research, 2023)
This study investigated experimentally the flexural strength of no-fines recycled aggregate concrete, produced using 20-70% replacement of conventional coarse aggregates with coarse aggregates from demolished waste. Six prisms in each dosage with a 1:4 mix and 0.5 water-binder ratios were prepared. A batch of prisms with conventional aggregates was also cast to compare them with the proposed concrete. An equal number of samples were cured for 7 and 28 days and tested under a gradually increasing central point load to examine failure load, central deflection, and flexural strength. The comparison of results showed an increasing trend in deflection with an increase in the dosage of recycled aggregates. The 7-day cured samples had approximately 2.6 times the deflection of conventional concrete. However, the deflection at all replacement levels remained less than that allowed by ACI-318. The results showed a decreasing trend in flexural strength with an increase in the dosage of recycled aggregates. The 40% replacement sample had a less than 20% strength reduction and is recommended as the optimum level of replacement of conventional aggregates for the production of no-fines recycled aggregate concrete.